Nilai-Nilai Kepemimpinan Putera Jaya Pati dalam Hikayat Raja Kalawandu - Tiara Eka Maharani; Asep Yudha Wirajaya (Madah: Jurnal Bahasa dan Sastra, 2024)
The Hikayat Raja Kalawandu is an ancient manuscript in the collection of the Houghton Library owned by Harvard University. This script, coded MS Indo 27, tells about the heroism of Putera Jaya Pati, who was the son of King Kalawandu. Putera Jaya Pati is described as a potential leader who has leadership values. It is necessary to study the manuscript entitled Hikayat Raja Kalawandu. This study aims to present the Hikayat Raja Kalawandu by knowing and expressing the leadership values ​​of Putera Jaya Pati. This study uses a qualitative descriptive method with a philological approach. The results of the analysis in this study indicate that there are 4 leadership values, namely the value of hard work, courage, intelligence, and religion. Therefore, the disclosure of leadership values ​​can be used as a source of insight and guidance for today's leaders.